ASSESSING THE INFLUENCE OF CROSS CULTURAL PRAGMATICS ON COMMUNICATION COMPETENCE IN MULTINATIONAL CONTEXTS - Dian Lestari; Fini Widya Fransiska; Bayu Grendo Sigarete (Education Studies and Teaching Journal (EDUTECH), 2024)
Cross-cultural pragmatic differences often constitute a major challenge in the development of communication competencies of multinational teams, hindering global organizational collaboration and productivity. This research aims to identify theoretical frameworks and key models that are relevant in explaining cross-cultural pragmatics and its impact on communication competence. Using a systematic literature review (SLR) approach with the PRISMA protocol, this research analyzed 38 academic articles from various geographic and cultural contexts. The results show that the theory of Cross-Cultural Pragmatics, the Intercultural Communication Competency Model, and High-Context and Low-Context Communication provide significant contributions in understanding and optimizing cross-cultural communication. This research recommends theory-based training to increase communication effectiveness in multinational organizations.